Etika dan Moral dalam Penanganan Orang dengan Gangguan Jiwa dalam Perspektif Islam - Salmaa Alfisyah Faza; Firda Noor Rahmatin; Aisha Halwa Nazhifa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Handling of people with mental disorders has received serious attention from various perspectives, including in Islam which views it with a comprehensive view. The background of this study focuses on how Islam instructs its followers to treat individuals with mental disorders, as well as the humanitarian values ​​emphasized by religion in the aspect of handling. The purpose of this study is to explore the Islamic view on handling people with mental disorders, and to gain a deeper understanding of the guidance given by Islam in this regard. The research method is a literature review that critically examines the body of academic literature. The nature of this study is descriptive analysis, where related data is systematically and orderly analyzed to provide a good understanding to the reader. Qualitative data in the form of written language was obtained from journals and articles, and analyzed through a concise content analysis. The findings of the study indicate that Islam provides strong ethical guidance as well as practical behavior in handling individuals with mental disorders, which can make a positive contribution to the modern approach in psychiatry and mental health services. The implications of this study provide new insights into the integration of mental health approaches with religious values ​​that offer a holistic approach to the individual.